Experimental investigation of the dynamic characteristics of wrapped and wound fiber and metal/fiber reinforced composite pipes. (15th November 2021) - Gowid, Samer; Mahdi, Elsadig; Youssef, Sabry S.; Moustafa, Essam; Mosleh, Ahmed; Shokry, Abdallah
Abstract: This paper experimentally investigates the effect of the manufacturing method and metal reinforcement option on the natural frequency and damping behavior of five polymer and Fiber Reinforced Polymer (FRP) composite pipes. The five pipes are made of polymer, roll-wrapped woven glass FRP, metal-reinforced roll-wrapped woven glass FRP, filament-wound glass FRP, and metal reinforced filament-wound-up glass FRP. The composite pipes can replace conventional pipes in oil and gas industries and conventional metallic shafts in many applications. Logarithmic decay, logarithmic decrement, and random frequency excitation methods were employed to identify the damping ratio and the natural frequency of the different composite materials. Tests were conducted using a CVMSL electrodynamic shaker (M437A/BT500M) and a triaxle vibration measurement instrument. The results revealed that the metal-reinforcement option outperformed the rest of the reinforcement options in terms of dynamic characteristics, as it resulted in higher natural frequencies and damping ratios. In addition, the filament-wound-up manufacturing method demonstrated superior dynamic characteristics over the woven roll-wrapped method. The metal/filament-wound-up reinforcement increased the logarithmic damping decrement from 0.1165 to 0.1231 and the natural frequency from 36.5 Hz to 70 Hz.